2012
DOI: 10.1042/bj20111360
|View full text |Cite
|
Sign up to set email alerts
|

A molten globule-to-ordered structure transition of Drosophila melanogaster crammer is required for its ability to inhibit cathepsin

Abstract: Drosophila melanogaster crammer is a novel cathepsin inhibitor that is involved in LTM (long-term memory) formation. The mechanism by which the inhibitory activity is regulated remains unclear. In the present paper we have shown that the oligomeric state of crammer is pH dependent. At neutral pH, crammer is predominantly dimeric in vitro as a result of disulfide bond formation, and is monomeric at acidic pH. Our inhibition assay shows that monomeric crammer, not disulfide-bonded dimer, is a strong competitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…ANS, indeed, is well known to only bind to partially unfolded proteins, but not to native or completely denatured ones (Tseng et al, 2012). As a consequence, we observed that ANS did not bind to any of the tested proteins at neutral pH.…”
Section: E-64/ficin E Molar Raɵomentioning
confidence: 74%
“…ANS, indeed, is well known to only bind to partially unfolded proteins, but not to native or completely denatured ones (Tseng et al, 2012). As a consequence, we observed that ANS did not bind to any of the tested proteins at neutral pH.…”
Section: E-64/ficin E Molar Raɵomentioning
confidence: 74%
“…Conventionally, the exposed hydrophobic clusters of folding intermediates are detected through 1-anilino-8-naphthalene sulfonate (ANS) binding, a much utilized fluorescence probe for detecting the non-polar character of proteins and membranes [14]. In fact, the available literature reveals that molten globule state is mostly pinpointed from its maximum ANS binding ability under the conditions studied since the other typical features viz pronounced secondary structure and disrupted tertiary contacts often seem to merge with intermediates lying in the vicinity of MG-state [12], [15][20]. Such utilization of ANS which is based upon the principle that ANS is practically non fluorescent in water but produces brilliant fluorescence upon binding to hydrophobic sites of protein [21] generally ignores the contribution of sulfonate group that was earlier considered as a mere solublizing agent for otherwise almost water-insoluble anilino-naphthalene moiety.…”
Section: Introductionmentioning
confidence: 99%
“…These residues are located in the α-helix 1 (W9, Y12, F16), loop 1 (Y20), and the α-helix 2 (Y32) for hydrophobic Core 1, and the α-helix 2 (F46) and loop 2 (W53) for the hydrophobic Core 2 (Figure 1). Four salt bridges have been reported to connect the α-helices [43]. D6-R29 and E8-K36 connect the α-helices 1 and 2, while E24-R28 and R28-E67 connect the α-helices 2 and 4.…”
Section: Resultsmentioning
confidence: 99%
“…DCTSL, propeptide of Drosophila cathepsin L. HCTSL, HCTSK, and HCTSS, propeptides of human cathepsin L, K, and S. ( B ) 3D structure of crammer shown as a ribbon diagram. The coordinates were taken from the Protein Data Bank (PDB) with the accession code of 2KTW [43]. The mutated residues in this study appear as spheres for the aromatic residues of hydrophobic Cores 1 and 2, and as sticks for the salt bridges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation